Effect of plant growth regulators on plant regeneration of hyacinth bean (Lablab purpureus (L.) Sweet) through nodal explants (Bangladesh Journal of Agricultural Research, 2019)
Nodal explants of three accessions namely BD-101, BD-122 and BD-8001 of hyacinth bean (Lablab purpureus (L.) Sweet) were cultured for four weeks on MS medium supplemented with different concentrations and combinations of NAA (0, 0.1 mgl-1) and BAP (0.5, 1.0 and 2.5 mgl-1) for plant regeneration. The highest shoot initiation was observed in 0.5 mgl-1 BAP while the lowest shoot initiation was found in 2.5 mgl-1 BAP with 0.1 mgl-1 NAA. Earlier shoot initiation was exhibited in 0.5 mgl-1 BAP with 0.1 mgl-1 NAA. The highest number of leaflets and higher shoot lengths were observed in MS medium. Comparatively higher number of shoots was found in BAP (0.5-2.5 mgl-1). The highest percentage of callus was initiated in medium supplemented with 1.0 mgl-1 BAP. Earlier callus initiation and larger callus size were found in combination of BAP (0.5-2.5 mgl-1) with 0.1 mgl-1 NAA. BD-122 cultured in MS medium was found superior for shoot regeneration through node culture. Four different concentrations of IBA (0.1-1.5 mgl-1) were used for rooting. The highest percentage (86.67 %) of rooting was found in MS medium containing 0.1 mgl-1 IBA at four weeks. Rooting frequency decreased with the increasing concentration of IBA. The accession BD-8001 had 99.60 % rooting in 0.5 mgl-1 IBA. The highest number of longest roots was exhibited in 0.1 mgl-1 IBA. The regeneration protocol developed from nodal explants has applicability in improvement of hyacinth bean.Bangladesh J. Agril. Res. 44(1): 27-42, March 2019